Engineering 2D material interfaces at the nanoscale for advanced functionality; СХС-2025 - Rodriguez (Rodriges) Contreras R. D. Raul David; Tran Tuan Hoang О. В.; Cheshev D. L. Dmitry Leonidovich; Sheremet E. S. Evgeniya Sergeevna (2025, 2025)
Текстовый файл